The relevance of knowledge, perception, and factors that influence contraceptive use among married women living in Uaddara Barracks, Ghana - Lumor, Daisy Afra; Obirikorang, Christian; Acheampong, Emmanuel; Obirikorang, Yaa; Owusu, Hubert; Newton, Sam (Frontiers in Global Women's Health, 2023)
Background Contraceptive use has many advantages for personal growth and societal advancement, but there is still the problem of unmet needs for women, which highlights the gap between women's reproductive intentions and contraceptive use. This study investigated knowledge, perceptions, and factors that influence contraceptive use among married women living in a military base in Ghana. Methods This cross-sectional study involved 350 married women between the ages of 20 and 58 years at the Uaddara Barracks, Kumasi. A structured questionnaire was used to collect information on the background, knowledge, perceptions on contraceptive use, and contraceptive methods used by participants. Data was entered into an Excel sheet and analysed using R version 4.2.1. Results Most of the participants were between the age range of 36 and 40 years (25.5%). Almost all study participants (97.4%), had heard about contraceptives with 80.6% showing a high level of knowledge on contraceptives. The majority of the women (84.6%) had previously used some form of contraceptives and 53.1% presently do. More than half of the participants (69.4%) had a positive perception of contraceptive use; 80.6% responded it was their own decision to use contraceptives, and 80.3% had the support of their husbands. Husbands' support of contraception resulted in a 5 times higher usage of contraceptives among women (aOR = 5.35; p < 0.001) while women who were married to military men were 45% (aOR = 0.45; p = 0.007) less likely to use contraceptive when compared to civilian wives. Demographic characteristics like being above 40 years (aOR = 0.25; p = 0.014), being a housewife (aOR = 0.42; p = 0.043) and working in the private sector (aOR = 0.33; p = 0.015) were significantly linked with less contraceptive use. Conclusion The study showed that women used contraceptives at a rate that was much higher than the national norm at the Uaddara Barracks, demonstrating the beneficial influence men had on women's contraceptive use. This thereby underscores the need for interventional policies that prioritized the male as much as women, while emphasizing the benefits of contraceptive use to the family and not just as an awareness program only.